Screening Of A High Glutaminolytic Enzyme Producing Strain And Its Extracellular Production By Solid State Fermentation - K. NATHIYA,; SOORAJ. S. NATH,; J. ANGAYARKANNI,; M. PALANISWAMY, (International Journal of Pharma and Bio Sciences, 2011)
This study presents new and alternative fungal strains for the production of glutaminolytic enzyme which has great potential to use in industrial and biotechnological processes. Forty fungal strains isolated from food and other sources were screened using minimal glutamine agar containing L-glutamine and phenol red as indicator for glutaminase production. All the strains were positive for glutaminase activity in a rapid-plate assay, as evidenced by pink halos. The cultivation of the best strain (Trichoderma harzianum) by solid state fermentation resulted in high quantities of extracellular glutaminolytic enzyme (88 U/g) with a zone of 1.2 cm when cultured at 30 °C for 5 days.